An assessment of RVM sisters' graduate theses in education to determine the extent of implementation and non-implementation of recommendations - Taylaran, Maria Florita, RVM (Animo Repository, 1982)
Growth of research in education has been one of the outstanding characteristics of cultural progress during the present century. This growth is evidenced by the continued appearance of new courses dealing with educational problems., the increased number of theses accpeted each year in graduate schools, and new grants for research. This study is an assessment of RVM Sisters' Graduate Theses in education to determine the extent of implementation and non-implementation of recommendations. It is an attempt to give a descriptive picture of the present status of the educational theses written by the RVM Sisters, with a special focus on the recommendations. The study aims to answer the following questions:1. What have been the problem areas covered by recommendations of the educational theses written by the RVM sisters?2. How many recommendations have been implemented?3. How many recommendations have not been implemented?4. What are the reasons for the non-implementation of recommentations?The RVM Sisters have been encouraged to do graduate studies particularly to do research work which will help improve the quality of education in the RVM schools.